Carbon-coated fast ion conductor modified positive electrode material and preparation method thereof
By carbon coating on the fast ion conductor and coating boric acid glassy compounds, the problems of reduced electron conductors and carbon escape caused by fast ion conductor coating are solved, and the synchronous improvement of ion and electronic conductivity of the positive electrode material is achieved. Improves battery performance and safety.
Patent Information
- Application Number
- CN202411287384.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, after the fast ion conductor is coated on the surface of the positive electrode material, the characteristics of the electronic insulator are reduced, and the electronic conductivity of the positive electrode material is easily escaped during the coating process, affecting battery performance and safety.
Using carbon-coated modified fast ion conductors and coated with boric acid glass compounds on its surface, the positive electrode material with LiaNixCoyMnzO2·cA·dB structure is prepared by ball milling and sintering processes, which synchronizes the ion and electron conductivity and prevents Carbon escape.
The synchronous improvement of the ionic conductivity and electronic conductivity of the positive electrode material is achieved, the battery performance and safety performance are improved, and the problem of carbon coating escape is avoided.
Smart Images

Figure CN119252881A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon-coated fast ion conductor modified positive electrode material and a preparation method thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] Lithium-ion batteries have become an indispensable component of the energy economy in the 21st century. However, the core issue in the application of lithium-ion batteries in large-scale battery fields such as automobiles and energy storage is still safety. Volatile, flammable and explosive organic electrolytes are the main factors causing safety problems of lithium-ion batteries. Therefore, using fast ion conductor solid electrolytes instead of electrolytes to develop all-solid-state lithium-ion batteries is an effective way to solve battery safety problems.
[0003] At present, all-solid-state batteries have not yet been commercialized, so people have proposed new applications for fast ion conductors, coating them on the surface of positive electrode materials to inhibit the side reactions between positive electrode materials and electrolytes and improve the safety of battery systems. This idea is also a direction that is currently being studied more. The traditional process is to coat the fast ion conductor and then stabilize it on the surface of the positive electrode material through a sintering process, but this also brings a new problem. The fast ion conductor is a very good ion-conducting material, but its ability to conduct electrons is biased, and it can be said to be an electronic insulator, which also brings difficulties to the simple coating of fast ion conductors. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention proposes a carbon-coated fast ion conductor modified positive electrode material and a preparation method thereof. The method uses a carbon-coated modified fast ion conductor to modify the positive electrode material, and at the same time uses the characteristics of the boric acid glass state to coat the surface of the carbon-coated fast ion conductor, thereby effectively preventing the escape of carbon in the carbon-coated fast ion conductor, and achieving the simultaneous improvement of the ionic conductivity and electronic conductivity of the positive electrode material.
[0005] The technical solution of the present invention is: a carbon-coated fast ion conductor modified positive electrode material, the chemical formula of which is Li a Ni x Co y Mn z O2·cA·dB, wherein, 1.00≤a≤1.20, 0.00<c≤0.01, 0.00<d≤0.02, 0.00≤x<1.00, 0.00≤y<0.2, 0.00≤z<0.4, x+y+z=1; A is the first coating, B is the second coating, the first coating A is a carbon-coated fast ion conductor; the second coating B is an anti-carbon escape compound.
[0006] Preferably, the carbon escape prevention compound is in a glassy, molten or liquid state at 250-450° C., and is in a solid state at room temperature.
[0007] Preferably, the carbon escape prevention compound is boric acid.
[0008] Preferably, the fast ion conductor is LATP or LLZO.
[0009] Preferably, the positive electrode material contains total free lithium <1500 ppm by mass.
[0010] Preferably, its specific surface area is 0.5 to 1.2 m 2 / g.
[0011] Preferably, the average particle size of the positive electrode material is 2 to 5 μm.
[0012] The second object of the present invention is to provide a positive electrode material for a lithium ion battery, wherein the positive electrode active material comprises the above-mentioned carbon-coated fast ion conductor modified positive electrode material.
[0013] The third object of the present invention is to provide a lithium ion battery, which comprises the above-mentioned lithium ion battery positive electrode material.
[0014] A fourth object of the present invention is to provide an electrical device comprising the above-mentioned lithium-ion battery, wherein the lithium-ion battery is used to provide electrical energy.
[0015] A fifth object of the present invention is to provide a method for preparing a carbon-coated fast ion conductor modified positive electrode material, comprising the following steps: Step 1: Mix the ternary cathode material, the carbon-coated fast ion conductor and the carbon escape prevention compound in a mass ratio of 1.0: (0.001-0.02): (0.006-0.01) and then ball mill; Step 2: Place the ball-milled material into a muffle furnace, heat the temperature to 250-450° C. at a heating rate of 5° C. / min in an air atmosphere, and sinter for 6 hours to obtain a carbon-coated fast ion conductor modified positive electrode material.
[0016] Preferably, the carbon escape prevention compound is boric acid.
[0017] Due to the adoption of the above technical solution, the advantages of the present invention are: 1. The present invention uses a carbon-coated fast ion conductor to modify the positive electrode material, so that the ionic conductivity and electronic conductivity of the positive electrode material are improved simultaneously, thereby improving the battery performance.
[0018] 2. The present invention adopts boric acid for simultaneous coating, which solves the problem of carbon escape during the coating process.
[0019] 3. The lithium-ion battery positive electrode material of the present invention improves the safety performance of the battery through double coating modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the carbon-coated fast ion conductor modified positive electrode material of the present invention; Figure 2 It is the DSC curve diagram of Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0021] In order to better understand the technical solutions of the embodiments of the present application, they are further described below in conjunction with some preferred embodiments of the present application.
[0022] In this specification, amounts, ratios and other numerical values are sometimes presented herein in a range format. It should be understood that such a range format is used for convenience and brevity, and should be flexibly understood to include not only the values explicitly specified as range limits, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0023] The chemical formula of the carbon-coated fast ion conductor modified positive electrode material proposed in this application is Li a Ni x Co y Mn z O2·cA·dB, wherein, 1.00≤a≤1.20, 0.00<c≤0.01, 0.00<d≤0.02, 0.00≤x<1.00, 0.00≤y<0.2, 0.00≤z<0.4, x+y+z=1; A is the first coating, B is the second coating, the first coating A is a carbon-coated fast ion conductor; the second coating B is an anti-carbon escape compound.
[0024] Preferably, the carbon escape prevention compound is in a glassy, molten or liquid state at 250-450° C., and is in a solid state at room temperature.
[0025] Preferably, the carbon escape prevention compound is boric acid.
[0026] Preferably, the fast ion conductor is LATP or LLZO.
[0027] Preferably, the positive electrode material contains total free lithium <1500 ppm by mass.
[0028] Preferably, its specific surface area is 0.5 to 1.2 m 2 / g.
[0029] Preferably, the average particle size of the positive electrode material is 2 to 5 μm.
[0030] The second object of the present invention is to provide a positive electrode material for a lithium ion battery, wherein the positive electrode active material comprises the above-mentioned carbon-coated fast ion conductor modified positive electrode material.
[0031] The third object of the present invention is to provide a lithium ion battery, which comprises the above-mentioned lithium ion battery positive electrode material.
[0032] A fourth object of the present invention is to provide an electrical device comprising the above-mentioned lithium-ion battery, wherein the lithium-ion battery is used to provide electrical energy.
[0033] The lithium-ion battery of the present invention is composed of electrodes, non-aqueous electrolytes, separators and containers. Specifically, the electrodes include positive electrodes and negative electrodes, the positive electrode is made of materials including positive electrode current collectors and positive electrode active materials coated on the positive electrode current collectors, conventional adhesives, conventional conductive additives and the like, the positive electrode active materials are the lithium-ion positive electrode materials of the present invention, and the negative electrode is made of materials including current collectors and conventional negative electrode active materials coated on the current collectors, conventional adhesives, conventional conductive additives and the like; the separator is a PP / PE film commonly used in the industry, which is used to separate the positive electrode from the negative electrode; the container is a container for the positive electrode, the negative electrode, the separator and the electrolyte.
[0034] A fifth object of the present invention is to provide a method for preparing a carbon-coated fast ion conductor modified positive electrode material, comprising the following steps: Step 1: Mix the ternary cathode material, the carbon-coated fast ion conductor and the carbon escape prevention compound in a mass ratio of 1.0: (0.001-0.02): (0.006-0.01) and then ball mill; Step 2: Place the ball-milled material into a muffle furnace, heat the temperature to 250-450° C. at a heating rate of 5° C. / min in an air atmosphere, and sinter for 6 hours to obtain a carbon-coated fast ion conductor modified positive electrode material.
[0035] Preferably, the carbon escape prevention compound is boric acid.
[0036] The carbon-coated fast ion conductor modified positive electrode material and its preparation method and application described in the present invention are explained below through specific embodiments. The reagents or instruments not described in the present application text are all contents that can be routinely confirmed by ordinary technicians in this field.
[0037] The reagents used in the following examples are shown in Table 1.
[0038] Table 1 Information on reagents used in the examples of the present invention
[0039] The equipment and analysis methods used in the following examples are as follows: The specific surface area was analyzed and tested using a fully automatic specific surface and porosity analyzer (TriStar Ⅱ 3020, Murray McTicker Co., Ltd., USA).
[0040] The test method for free lithium in positive electrode materials is as follows: Weigh an appropriate amount of sample (about 30 g) accurately to 0.01 g; place the sample in a 250 mL conical flask, add a magnetic stirring bar, and add 100 mL of deionized water; place the conical flask on a magnetic stirrer, turn on the stirrer and stir for 30 minutes; filter the mixed solution with filter paper and funnel; use a 50 mL pipette to transfer 50 mL of filtrate, place it in a 100 mL beaker, and add a magnetic stirring bar; place the beaker on a magnetic stirrer and add 2 drops of phenolphthalein indicator; titrate with 0.05 mol / L hydrochloric acid standard titration solution until the color of the solution changes from red to colorless; record 0.05 mol / L The volume of the hydrochloric acid standard titration solution is V1 (end point 1); add 2 drops of methyl red indicator and the color changes from colorless to yellow; titrate with 0.05mol / L hydrochloric acid standard titration solution until the color of the solution changes from yellow to orange; place the beaker on the heating furnace and heat until the solution boils (the color of the solution changes from orange to yellow); remove the 100mL beaker and cool to room temperature; place the beaker on the magnetic stirrer again; titrate with 0.05mol / L hydrochloric acid standard titration solution until the color of the solution changes from yellow to light red, and record the volume of 0.05mol / L hydrochloric acid standard titration solution V2 (end point 2); Lithium hydroxide: LiOH (wt%) = [V2-2 × (V2-V1)] × 0.05 × 23.946 × 2 × 100 / (m × 1000) Lithium carbonate: Li2CO3 (wt%) = (V2-V1) × 0.05 × 73.886 × 2 × 100 / (m × 1000) Free lithium: Li + (wt%)=V2×0.05×6.94×2×100 / (m×1000) m – mass of sample in g; V1 – first titration endpoint; V2 – second titration endpoint.
[0041] Average particle size test: MS3000 laser particle size analyzer is used for testing, the method is as follows: Take an appropriate amount of sample in a 100ml beaker, first rinse along the inner wall of the beaker with a wash bottle, then rinse the sample stuck to the bottom of the beaker with a wash bottle, and control the amount of pure water added to the beaker to 20~30mL, and the ultrasonic time is 5min (stir for 10s before, during and after ultrasonication, and the stirring rate is about 2r / s). Add 100±10ml of pure water to the injector of the MS3000 laser particle size analyzer, adjust the speed to 3000r / min, click start, and the instrument will automatically align the light and measure the background and wait for prompts to operate. Transfer the sample after ultrasonication to the stirring tank, and then rinse the beaker with a wash bottle to ensure that all samples are transferred. After the sample is completely added, the software automatically starts measuring. After the measurement is completed, the data is automatically saved.
[0042] DSC test method: STA449F3, heating rate 10℃ / min, cut-off temperature 400℃, test under nitrogen conditions.
[0043] Resistivity test: Suzhou Jingge ST-2255 was used to test the resistivity, with a pressure of 50Mpa and a sample weight of 5g.
[0044] In the following examples, the method for making a full battery (battery cell model 454261) using the positive electrode material prepared by the present invention is as follows: Positive electrode preparation: The positive electrode material of the present invention, conductive carbon black (SP), and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) (the weight ratio of the positive electrode material to NMP is 2.1:1) in a weight ratio of 94:3:3, and are fully mixed, stirred to form a uniform slurry, coated on an aluminum foil current collector, dried, and pressed into a pole sheet.
[0045] Negative electrode preparation: Add negative electrode artificial graphite, conductive carbon black (SP), carboxymethyl cellulose (CMC), and adhesive (SBR) in a weight ratio of 95:1:1:3 into sufficient pure water, stir to form a uniform slurry, coat it on the copper foil current collector, dry and press into a pole piece.
[0046] The diaphragm is a three-layer composite film material of PP / PE / PP.
[0047] The pressed positive and negative electrode sheets are spot welded to the upper pole ears, and after inserting the diaphragm, they are wound on the winder and loaded into the soft package fixture, and the top and side are sealed. Then, they are placed in an oven for baking, and then 9g of electrolyte is injected in an environment with a relative humidity of less than 1.5%. After the electrolyte is injected and formed for 48 hours (Zhejiang Hangke LIP-3AHB06 high constant temperature formation system), vacuum sealing is performed.
[0048] The sample drying and battery high temperature testing were carried out using the Dongguan Kerui Electromechanical KPBAK-03E-02 high-efficiency vacuum drying oven.
[0049] The charge and discharge test of the lithium-ion secondary battery prepared by the present invention is tested on a Wuhan Blue Electric battery tester (Wuhan Blue Electric CT2001C testing equipment) according to the test method of GB / T18287-2000. Due to different battery systems, the cycle retention rate of the material is greatly affected. The battery system used in this experiment is the most common evaluation system, that is, a 1 mol / L lithium hexafluorophosphate solution is used as the electrolyte, and the solvent in the lithium hexafluorophosphate solution is a mixed solvent with a mass ratio of dimethyl carbonate (DMC): ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1:1, and a mixture of artificial graphite and conductive carbon black, carboxymethyl cellulose and adhesive in a weight ratio of 95:1:1:3 is used as the negative electrode material, and the battery model is 454261, so as to expose the actual defects of the positive electrode material as soon as possible and determine the performance of the positive electrode material.
[0050] Example 1 Select LiNi 0.5 Co 0.2 Mn 0.3 O2 is used as the matrix material, and the mass ratio of matrix material: carbon-coated LLZO: boric acid is 1.0:0.01:0.008. The corresponding amount of carbon-coated LLZO and boric acid are weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 450℃ at a heating rate of 5℃ / min in an air atmosphere, and then sintered for 6 hours. The mixture is cooled to room temperature and sieved with a 300-mesh metal screen to obtain the positive electrode material 1.
[0051] The positive electrode material 1 was tested for particle size, specific surface area, free lithium and battery, and the data are shown in Table 2.
[0052] Example 2 Select LiNi 0.6 Co 0.1 Mn 0.3 O2 is used as the matrix material, and the mass ratio of matrix material: carbon-coated LATP: boric acid is 1.0:0.02:0.01. The corresponding amount of carbon-coated LATP and boric acid are weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 410℃ at a heating rate of 5℃ / min in an air atmosphere, and then sintered for 6 hours. The mixture is cooled to room temperature and sieved with a 300-mesh metal screen to obtain the positive electrode material 2.
[0053] The positive electrode material 2 was tested for particle size, specific surface area, free lithium and battery, and the data are shown in Table 2.
[0054] Example 3 Select LiNi 0.7 Co 0.1 Mn 0.2O2 is used as the matrix material, and the mass ratio of matrix material: carbon-coated LLZO: boric acid is 1.0:0.005:0.007. The corresponding amount of carbon-coated LATP and boric acid are weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 370℃ at a heating rate of 5℃ / min in an air atmosphere, and then sintered for 6 hours. The mixture is cooled to room temperature and sieved with a 300-mesh metal screen to obtain positive electrode material 3.
[0055] The positive electrode material 3 was tested for particle size, specific surface area, free lithium and battery, and the data are shown in Table 2.
[0056] Example 4 Select LiNi 0.83 Co 0.07 Mn 0.1 O2 is used as the matrix material, and the mass ratio of matrix material: carbon-coated LATP: boric acid is 1.0:0.001:0.008. The corresponding amount of carbon-coated LATP and boric acid are weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 320℃ at a heating rate of 5℃ / min in an air atmosphere, and then sintered for 6 hours. The mixture is cooled to room temperature and sieved with a 300-mesh metal screen to obtain the positive electrode material 4.
[0057] The positive electrode material 4 was tested for particle size, specific surface area, free lithium and battery, and the data are shown in Table 2.
[0058] Example 5 Select LiNi 0.92 Co 0.05 Mn 0.03 O2 is used as the matrix material, and the mass ratio of matrix material: carbon-coated LATP: boric acid is 1.0:0.008:0.006. The corresponding amount of carbon-coated LATP and boric acid are weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 250℃ at a heating rate of 5℃ / min in an air atmosphere, and then sintered for 6 hours. The mixture is cooled to room temperature and sieved with a 300-mesh metal screen to obtain the positive electrode material 5.
[0059] The positive electrode material 5 was tested for particle size, specific surface area, free lithium and battery. The data are shown in Table 2.
[0060] Comparative Example 1 Select LiNi 0.6 Co 0.1 Mn 0.3O2 is used as the matrix material, and the mass ratio of matrix material: LATP is 1.0:0.02. The corresponding amount of LATP is weighed and added to the matrix for ball milling. The ball milling is carried out at a rotation speed of 40HZ for 10 minutes. The evenly mixed materials are put into a muffle furnace, and the temperature is increased to 400℃ at a heating rate of 5℃ / min in an air atmosphere and sintered for 6 hours. The materials are cooled to room temperature and sieved with a 300-mesh metal screen to obtain the comparative positive electrode material D1.
[0061] The comparative positive electrode material D1 was subjected to particle size, specific surface area, free lithium and battery tests, and the data are shown in Table 2.
[0062] Table 2 Characterization data of the positive electrode materials obtained in the examples
[0063] In Table 2, the positive electrode materials prepared in the embodiments of the present invention have a total free lithium content of <1500ppm and a specific surface area of 0.6 to 1.0 m 2 / g, and the particle size is between 3.0 and 5.0μm.
[0064] At present, lithium battery safety issues frequently occur, and the side reaction of the electrolyte is the main reason. Solid-state batteries cannot be commercialized in a short time, so it is necessary to improve the interface of the positive electrode material. Including metal oxides, anion salt coating, etc., these coatings will reduce the ionic conductivity of the positive electrode material to a certain extent. In order not to reduce the ionic conductivity while coating, fast ion conductors are only used as coating agents, which are favored by scholars, but fast ion conductor coating will reduce the electronic conductivity of the positive electrode material. In order to solve the above problems, the present invention uses a carbon-coated modified fast ion conductor to modify the positive electrode material, achieving the simultaneous improvement of the ionic conductivity and electronic conductivity of the positive electrode material, and at the same time using the characteristics of the boric acid glass state to be coated on the surface of the carbon-coated fast ion conductor, effectively preventing the escape of carbon in the carbon-coated fast ion conductor.
[0065] It can be seen from Table 2 that in the embodiment, when the Ni molar fraction is 0.6, the peak value of the DSC of the positive electrode material using a carbon-coated fast ion conductor is increased by about 10°C compared to using only a fast ion conductor, and the powder resistivity is reduced by an order of magnitude, which significantly improves the electronic conductivity and safety.
[0066] In summary, the positive electrode material of the present invention achieves simultaneous improvement of the ionic conductivity and electronic conductivity of the positive electrode material, thereby improving the safety of the battery.
Claims
1. A carbon-coated fast ion conductor modified positive electrode material, characterized in that: Its chemical formula is Li a Ni x Co y Mn z O2·cA·dB, wherein, 1.00≤a≤1.20, 0.00<c≤0.01, 0.00<d≤0.02, 0.00≤x<1.00, 0.00≤y<0.2, 0.00≤z<0.4, x+y+z=1; A is the first coating, B is the second coating, the first coating A is a carbon-coated fast ion conductor; the second coating B is an anti-carbon escape compound.
2. The carbon-coated fast ion conductor modified positive electrode material according to claim 1, characterized in that: The carbon escape prevention compound is in a glassy state, a molten state or a liquid state at 250-450° C. and is in a solid state at room temperature.
3. The carbon-coated fast ion conductor modified positive electrode material according to claim 2, characterized in that: The carbon escape prevention compound is boric acid.
4. The carbon-coated fast ion conductor modified positive electrode material according to claim 1, characterized in that: The fast ion conductor is LATP or LLZO.
5. The carbon-coated fast ion conductor modified positive electrode material according to any one of claims 1 to 4, characterized in that: The positive electrode material contains total free lithium <1500 ppm by mass.
6. The carbon-coated fast ion conductor modified positive electrode material according to claim 5, characterized in that: Its specific surface area is 0.5~1.2m 2 / g.
7. The carbon-coated fast ion conductor modified positive electrode material according to claim 6, characterized in that: The average particle size is 2 to 5 μm.
8. A positive electrode material for a lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises the carbon-coated fast ion conductor modified positive electrode material according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: It comprises the lithium ion battery positive electrode material as claimed in claim 8.
10. An electrical equipment, characterized in that: It comprises the lithium ion battery as claimed in claim 9, wherein the lithium ion battery is used to provide electrical energy.
11. A method for preparing a carbon-coated fast ion conductor modified positive electrode material, characterized in that The following steps are involved: Step 1: Mix the ternary cathode material, the carbon-coated fast ion conductor and the carbon escape prevention compound in a mass ratio of 1.0: (0.001-0.02): (0.006-0.01) and then ball mill; Step 2: Place the ball-milled material into a muffle furnace, heat the temperature to 250-450° C. at a heating rate of 5° C. / min in an air atmosphere, and then sinter for 6 hours to obtain a carbon-coated fast ion conductor modified positive electrode material.
12. The carbon-coated fast ion conductor modified positive electrode material according to claim 11, characterized in that: The carbon escape prevention compound is boric acid.
